Genomic selection in algae with biphasic lifecycles: A Saccharina latissima (sugar kelp) case study - Huang, Mao; Robbins, Kelly R.; Li, Yaoguang; Umanzor, Schery; Marty-Rivera, Michael; Bailey, David; Aydlett, Margaret; Schmutz, Jeremy; Grimwood, Jane; Yarish, Charles; Lindell, Scott; Jannink, Jean-Luc (Frontiers in Marine Science, 2023)
Sugar kelp (Saccharina latissima) has a biphasic life cycle, allowing selection on both the diploid sporophytes (SPs) and haploid gametophytes (GPs). We trained a genomic selection (GS) model from farm-tested SP phenotypic data and used a mixed-ploidy additive relationship matrix to predict GP breeding values. Top-ranked GPs were used to make crosses for further farm evaluation. The relationship matrix included 866 individuals: a) founder SPs sampled from the wild; b) progeny GPs from founders; c) Farm-tested SPs crossed from b); and d) progeny GPs from farm-tested SPs. The complete pedigree-based relationship matrix was estimated for all individuals. A subset of founder SPs (n = 58) and GPs (n = 276) were genotyped with Diversity Array Technology and whole genome sequencing, respectively. We evaluated GS prediction accuracy via cross validation for SPs tested on farm in 2019 and 2020 using a basic GBLUP model. We also estimated the general combining ability (GCA) and specific combining ability (SCA) variances of parental GPs. A total of 11 yield-related and morphology traits were evaluated. The cross validation accuracies for dry weight per meter (r ranged from 0.16 to 0.35) and wet weight per meter (r ranged 0.19 to 0.35) were comparable to GS accuracy for yield traits in terrestrial crops. For morphology traits, cross validation accuracy exceeded 0.18 in all scenarios except for blade thickness in the second year. Accuracy in a third validation year (2021) was 0.31 for dry weight per meter over a confirmation set of 87 individuals.